Development of a functional ingredient rich in hesperidin from citrus fruit wastes (Research, Society and Development, 2021)
The peels of citrus fruits contain a high concentration of bioactive compounds. Among these compounds, hesperidin stands out for its beneficial health effects. This study had the objective of evaluating the hesperidin content in peel samples of different citrus fruit and to propose the development of a functional product obtained from these peels. The peels were lyophilized and had the total flavonoids analyzed by high-performance liquid chromatography. The peels of several fruits were dried in a microwave oven and ground in a blender to obtain a homogeneous powder. This material was submitted to extraction and quantification of hesperidin. The highest concentrations were found in the ‘Ponkan’ tangerine, ‘Murcott’ tangerine and ‘Navel’ orange, while the lowest were found in the ‘Sicilian’ lemon and ‘Lima’ orange. The functional ingredient obtained from the ground peels after microwave drying can be used for direct consumption or to enrich food preparations.